Inducing heat shock protein 70 expression provides a robust anti-thrombotic effect with minimal bleeding risk - Allende, Mikel; Molina, Eva; Lecumberri, Ramón; Sánchez-Arias, Juan Antonio; Ugarte, Ana; Guruceaga, Elizabeth; Oyarzabal, Julen; Hermida, José (Thrombosis and Haemostasis, 2017)
Antithrombotic medications target coagulation factors. Their use is associated with an increased bleeding risk. Safer drugs are needed. The heat shock protein 70 (Hsp70) exhibits antithrombotic properties that do not influence bleeding. By using murine models, we aimed to test the hypothesis that overexpressing Hsp70 with CM-695, a first in class dual inhibitor of HDAC6 and phosphodiesterase 9, protects against thrombosis while leaves bleeding tendency unaltered. CM-695 was used to induce Hsp70 overexpression. Hsp70 overexpressing mice were submitted to three thrombosis-triggering procedures. The ferric chloride carotid artery model was used to compare the antithrombotic role of CM-695 and rivaroxaban, a direct oral anticoagulant. The mouse tail transection model was used to compare the bleeding tendency upon CM-695 or rivaroxaban administration. Intraperitoneal (i. p.) 20 mg/kg CM-695 increased Hsp70 expression markedly in the murine aortic tissue. This treatment delayed thrombosis in the collagen/epinephrine [p=0.04 (Log-Rank test), n=10], Rose Bengal/laser [median vessel occlusion time (OT): 58.6 vs 39.0 minutes (min) in the control group (CG), p=0.008, n≥10] and ferric chloride (OT: 14.7 vs 9.2 min in the CG, p=0.032, n≥10) models. I.p. 80 mg/kg CM-695 (n≥9) and intravenous 3 mg/kg rivaroxaban (n≥8) significantly delayed thrombosis. CM-695 did not induce bleeding [median bleeding time (BT): 8.5 vs 7.5 min in the CG, n≥10]. However, BT was dramatically increased by rivaroxaban (30.0 vs 13.7 min in the CG, p=0.001, n=10). In conclusion, CM-695 is a new antithrombotic small molecule devoid of bleeding risk that may be envisioned as a useful clinical tool.
Keywords: Thrombosis; antithrombotics; haemorrhage